European Network of Gynaecological Oncological Trial Groups' Requirements for Trials Between Academic Groups and Industry Partners—First Update 2015. Issue 7 (September 2015) - du Bois, Andreas; Reuss, Alexander; Pujade-Lauraine, Eric; Pignata, Sandro; Ledermann, Jonathan; Casado, Antonio; Sehouli, Jalid; Mirza, Mansoor; Colombo, Nicoletta; Marth, Christian; Witteveen, Els; Del Campo, Jose; et al.
<x xml:space="preserve">Abstract</x> Abstract The first version of ENGOT's Requirements for Trials Between Academic Groups and Industry Partners in Europe was published 2010. This first update integrates the experiences made by the ENGOT network and the cooperative group studies while performing, analyzing, and publishing -among others - three large phase III trials. Furthermore, progress in European legislation and its impact on clinical studies in Europe have been considered in this update process.